Mexican Redrump Tarantula, Brachypelma vagans (Ausserer) (Arachnida: Araneae: Theraphosidae) - Glavis B. Edwards; Kenneth L. Hibbard (EDIS, 2004)
In early August 1996, a large black spider with red hairs on its abdomen was collected by citrus grove workers in St. Lucie County, Florida, west of Ft. Pierce. The workers gave the spider to a citrus survey crew, who brought it back to Gainesville. The first author examined the specimen (which was only half grown) and tentatively identified it as Brachypelma vagans (Ausserer), a species known to be commonly imported by the pet trade under assorted common names (Central American, Guatemalan, Honduran, or Mexican black velvet tarantulas). The accepted common name is Mexican redrump tarantula (Breene 1995). This document is EENY-287, originally published as DPI Entomology Circular 394, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2003.